2019
DOI: 10.1103/physrevb.100.245305
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic and hydrodynamic magnetotransport in narrow channels

Abstract: An increasing number of low carrier density materials exhibit a surprisingly large transport mean free path due to inefficient momentum relaxation. Consequently, charge transport in these systems is markedly non-ohmic but rather ballistic or hydrodynamic, features which can be explored by driving current through narrow channels. Using a kinetic equation approach we theoretically investigate how a non-quantizing magnetic field discerns ballistic and hydrodynamic transport, in particular in the spatial dependenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 49 publications
4
65
0
1
Order By: Relevance
“…Similar argument can be applied to the electric field. Magnetic field is typically not treated within linear response 15 leading to the field-dependent viscosity and Hall viscosity 8,16,[40][41][42] . Treating the time derivative in the Liouville's operator in the same manner leads to frequency-dependent dissipative coefficients.…”
Section: A Kinetic Theory Approachmentioning
confidence: 99%
“…Similar argument can be applied to the electric field. Magnetic field is typically not treated within linear response 15 leading to the field-dependent viscosity and Hall viscosity 8,16,[40][41][42] . Treating the time derivative in the Liouville's operator in the same manner leads to frequency-dependent dissipative coefficients.…”
Section: A Kinetic Theory Approachmentioning
confidence: 99%
“…heoretical and experimental studies have revealed that electrons in condensed matter can behave hydrodynamically, exhibiting fluid phenomena such as Stokes flow and vortices [1][2][3][4][5][6][7][8][9] . Unlike classical fluids, preferred directions inside crystals lift isotropic restrictions, necessitating a generalized treatment of electron hydrodynamics.…”
mentioning
confidence: 99%
“…As was shown in [36,38], in the presence of weak electron-electron scattering, in almost all magnetic fields below the critical one (B < B c ), specifically, when 2 − ω c W ≫ γW , the electron flow is ballistic. In this case, in the main order in the scattering rate γ, such flows are described by kinetic equation ( 6) with an omitted arrival term [36,38]:…”
Section: General Solution In the Ballistic Regimementioning
confidence: 60%
“…In the magnetic field B = B c , in which the diameter of the electron cyclotron orbit 2R c becomes equal to the sample width W and some electrons start to make a complete revolution without scattering at the edges, the longitudinal and Hall resistances as functions of the magnetic field experience a jump. In [38], the Poiseuille flow of 2D electrons in a magnetic field was studied in more detail; specifically, the Hall-field distributions over the sample cross section were numerically calculated for B < B c and B > B c and an analytical solution of the kinetic equation in the ballistic region B < B c was constructed. This allowed the authors to explain the evolution of the Hall-field profile curvature upon a variation in the magnetic field, which was observed experimentally in [10].…”
Section: Introductionmentioning
confidence: 99%